We Use Infusions of Lemon and Lemongrass to Maintain Endurance - Santo Marko Rapis; Merokos Bentali (Community Service Akseprin Journal, 2023)
Climate change, along with the post-pandemic scenario, renders the population's immune systems susceptible to different infections. Immunity can be sustained by hygiene, physical activity, and a balanced diet. Another method to sustain immunity is to ingest traditional herbal items or herbal remedies. A traditional beverage that is easy to prepare and uses readily available ingredients in the community is lemongrass stew. Lemons (Citrus lemons) possess antioxidant properties due to their vitamin C content, whilst lemongrass (Cymbopogon nardus L.) contains citral and geranial advantageous chemicals as anti-inflammatories. This workshop with participants aims to impart knowledge and insights regarding the advantages of lemongrass lemon drink and its preparation, which involves thoroughly washing the ingredients, boiling them with tamarind sugar and additional spices such as cinnamon and ginger, and subsequently filtering the mixture to produce a beverage that supports immune health. Participants exhibited considerable enthusiasm due to the activity's pertinent issue, with the expectation that it would enhance their comprehension of immunity maintenance, particularly throughout the transitional season and post-pandemic period. The conducted activities indicate that, based on pre- and post-event test results, comprehension of the workshop material has improved to 95%.